Hubungan Dukungan Sosial Terhadap Motivasi Belajar Mahasiswa: Studi Literatur - Deodor, Mardje Alianti; Morintoh, Febrilinsi; Kasingku, Juwinner Dedy; Frans, Nofry (JUPE : Jurnal Pendidikan Mandala, 2023)
Students play a crucial role as learners who constantly interact with various learning tasks assigned to them. Positive social support from various sources, such as close friends, parents, teachers, and individuals around them, can help students develop the ability to enhance their learning motivation. This study aims to examine the relationship between social support and learning motivation. It adopts a literature library research approach, utilizing samples derived from previous studies, both quantitative and qualitative in nature. The research data demonstrates a correlation between social support from various sources and learning motivation, encompassing the students. Despite having a relatively high level of low learning motivation, this can be attributed to insufficient social support. Among the findings, peer and parental support emerged as the most influential forms of social support based on the existing research overview.